Elevated activation of CaMKIIalpha in the CPEB3 knockout hippocampus impairs a specific form of NMDAR-dependent synaptic depotentiation - Huang, Wen-Hsuan; Chao, Hsu-Wen; Tsai, Li-Yun; Chung, Ming-Hung; Huang, Yi-Shuian (Frontiers in Cellular Neuroscience, 2014)
Cytoplasmic polyadenylation element binding protein (CPEB) 3 is a sequence-specific RNA-binding protein that confines the strength of glutamatergic synapses by translationally downregulating the expression of multiple plasticity-related proteins (PRPs), including the N-methyl-D-aspartate receptor (NMDAR) and the postsynaptic density protein (PSD) 95. CPEB3 knockout (KO) mice exhibit hippocampus-dependent abnormalities related not only to long-term spatial memory but also to the short-term acquisition and extinction of contextual fear memory. In this study, we identified a specific form of NMDAR-dependent synaptic depotentiation (DPT) that is impaired in the adult CPEB3 KO hippocampus. In parallel, cultured KO neurons also exhibited delayed morphological and biochemical responses under NMDA-induced chemical long-term depression (c-LTD). The c-LTD defects in the KO neurons include elevated activation of calcium/calmodulin-dependent protein kinase II alpha subunit (CaMKIIa), increased Ser831 phosphorylation of GluA1 and slow degradation of PSD95 and GluA1. Because transient pharmacological suppression of CaMKIIa activity during the DPT-initiating phase successfully reversed the long-term potentiation (LTP) in the KO hippocampus, DPT and c-LTD in the two different systems shared common molecular defects due to the absence of CPEB3. Together, our results suggest that CPEB3 deficiency imbalances NMDAR-activated CaMKIIa signaling, which consequently fails to depress synaptic strength under certain stimulation conditions.